Referral Description of Placenta Previa Cases at Dr. Soedarso Regional Hospital, Pontianak - Muhammad Naufal Abdurrochman; Emika Prastyan; Eka Ardiani Putri; Agil Wahyu Pangestu Putra; Tri Wahyudi (Journal of Community Health Provision, 2026)
Placenta previa is a condition during pregnancy where the placenta is positioned near or covering the cervix, potentially complicating delivery. Maternal mortality rates during specific periods and times identify causes of maternal death. Emergencies in pregnancy are exacerbated by delays in treatment processes, accessing appropriate healthcare facilities late, and receiving services from competent healthcare providers late. Quick responses include referrals when basic healthcare facilities lack supportive infrastructure for healthcare providers' actions. Research is conducted to provide an overview of referral cases of placenta previa in pregnant women during the 2020-2023 period at RSUD Dr. Soedarso Pontianak. Knowing the patient referral overview for cases of placenta previa at RSUD Dr. Soedarso Pontianak. The collected data were analyzed in the form of descriptive statistics, processed using Statistical Product and Service Solution (SPSS) software 26.0. Data analysis in this study utilized univariate analysis including frequency distribution in percentages to determine the frequency or mode (most frequent). The results from SPSS 26.0 processing indicated that: 90 patients were referred (68.7%), and 41 patients were not referred (31.3%). Age distribution: <20 years old, 1 person (0.8%); 20-35 years old, 87 people (66.4%); >35 years old, 43 people (32.8%). Infant status: Alive, 130 infants (99.2%); Deceased, 1 infant (0.8%). Employment status: Employed, 25 people (19.1%); Unemployed, 106 people (80.9%). Hemoglobin levels (Anemia): Very mild, 61 people (19.1%); Mild, 52 people (39.7%); Moderate, 12 people (9.2%); Severe, 6 people (4.6%). Conclusion: The mechanism and implementation of referral services for patients with placenta previa at RSUD Dr. Soedarso Pontianak run smoothly, as evidenced by the higher number of patients referred from primary healthcare facilities compared to those who came directly to the hospital.